INFLUENCE OF BENDING OF INTERFACE BORDERS ON THE CRYSTALLIZATION PROCESSES IN METALS - E. I. Marukovich; V. Ju. Stetsenko (Литьë и металлургия)
The comparative analysis of the processes of homogeneous and heterogeneous nucleation at crystallization of metals on undercoats with different bending of surface and interfacial surface tension is given. It is shown that the main mechanisms of nucleation processes at hardening of metals are homogeneous and heterogeneous ones on own undissolved nanocrystals, which can be in melt in a superfine and (or) colloid state for a comparatively long period.